2013
DOI: 10.1063/1.4832758
|View full text |Cite
|
Sign up to set email alerts
|

Power law and exponential ejecta size distributions from the dynamic fragmentation of shock-loaded Cu and Sn metals under melt conditions

Abstract: Large scale molecular dynamics (MD) simulations are performed to study and to model the ejecta production from the dynamic fragmentation of shock-loaded metals under melt conditions. A generic 3D crystal in contact with vacuum containing about 10 8 atoms and

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 70 publications
(111 reference statements)
2
35
0
1
Order By: Relevance
“…This peak corresponds to a local concentration of matter caused by the effects of surface tension which minimize the energy of the jet at its tip, as already mentioned in Ref. [26]. Note that the bulk density ~ 6500 mg/cm 3 is slightly below the nominal density of Sn because the metal releases and its temperature is high.…”
Section: The Continuum Point Of Viewmentioning
confidence: 88%
See 2 more Smart Citations
“…This peak corresponds to a local concentration of matter caused by the effects of surface tension which minimize the energy of the jet at its tip, as already mentioned in Ref. [26]. Note that the bulk density ~ 6500 mg/cm 3 is slightly below the nominal density of Sn because the metal releases and its temperature is high.…”
Section: The Continuum Point Of Viewmentioning
confidence: 88%
“…In particular the classical hydrodynamics approaches suffer a lack of modeling and characterization of the rheological behavior of metals after shock loading; and data on surface tension and viscosity are needed. To our knowledge, only recent MD simulations performed on atomistic systems allowed to provide directly from computations ejecta size distributions [25][26][27]. Particulate…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, in case where the defects are parallel grooves, Durand et al have recently used Molecular Dynamic (MD) simulations of large systems to show that the ejection process is as follows: (i) the ejected material forms sheets of liquid metal which go thinner and thinner; (ii) when sheets are sufficiently thin, holes appear and sheets break to form filaments; and (iii) those filaments stretch and finally break also to form spherical clusters. 1,4 It appears that the breaking of the sheets starts when the thickness is about several nanometers. So, to study the last parts of this phenomenon, microscopic simulations seem to be the good tool, and those MD simulations made possible to get the entire size distribution of the final spherical aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…The ejecta source and RM sheet breakup has also been studied extensively with MD simulations [55][56][57][58][59][60], and more research on dynamic particle sizing diagnostics is reported, works that includes holography and Mie scattering [61,62].…”
Section: Smentioning
confidence: 99%